The genus Cerithideopsis Thiele, 1929 (Gastropoda: Potamididae) in the Indo-West Pacific region - Reid, David G.; Claremont, Martine (Zootaxa, 2014)
The genus Cerithideopsis is most common in mangrove and salt marsh habitats of the New World tropics, but there is also a small radiation in the Indo-West Pacific region. Previously, these Indo-Pacific snails have generally been classified as Cerithidea largillierti (Philippi, 1848). Molecular phylogenetic analysis (partial sequences of mitochondrial COI and 16S rRNA, and nuclear 28S rRNA) of 15 specimens from 8 localities between Japan and Australia reveal three clades, among which there are small morphological differences and which show allopatric distributions. Cerithideopsis largillierti sensu stricto is restricted to Japan and China, while the two other species are described as new: C. australiensis occurs in tropical Australasia and C. malayensis is found from Malaysia to Java and the Philippines. All occur on mud and in pools with leaf litter, in the shaded landward and middle zones of mangrove forests, and do not climb the trees. The species accounts include full synonymies, detailed descriptions of shells based on 82 museum samples, descriptions of living animals, distribution records and maps, and notes on habitat and conservation status.